Dashboard Visualisasi Data UMK Sebagai Alat Pengambilan Keputusan Menggunakan Microsoft Power BI - Birra Lailatul Nafiisa; Yayang Novealita Wahono Putri; Qurratu Ayunin (Jurusan Akuntansi Politeknik Negeri Padang, 2022)
SME empowerment will directly increase productivity, increase people's per capita income, and provide jobs more evenly. Small Micro Enterprises contributed Rp 2,121.3 trillion to Gross Domestic Product from base Rp 335.1 trillion in previous year with a percentage of 53.6%. SMEs are currently faced with a very high product competitiveness era, relatively short product life cycles following market trends, and relatively fast product innovation capabilities. The lack of sources of capital is the main problem currently facing SMEs in Indonesia. By looking at the opportunities, challenges, and threats faced by MSEs in Indonesia, it is necessary to design a system that functions as a decision-making tool for interested parties. So the purpose is to design a dashboard using Business Intelligence as a decision-making tool. The method used to design this dashboard is ADDIE using Microsoft Power BI. The design result is a visualization dashboard for MSEs in Indonesia based on the number of businesses in the green economy sector, the number of businesses in all sectors, the number of workers, the amount of income, and the amount of expenditure. The results of this visualization dashboard can be a reference for investors to give funds to increase SME’s size and competitiveness.